2023
DOI: 10.3390/cells12081150
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Receptors and Their Involvement in Melanization of Sensory Cells in Ciona intestinalis

Abstract: Serotonin (5-hydroxytryptamine (5-HT)) is a biogenic monoamine with pleiotropic functions. It exerts its roles by binding to specific 5-HT receptors (5HTRs) classified into different families and subtypes. Homologs of 5HTRs are widely present in invertebrates, but their expression and pharmacological characterization have been scarcely investigated. In particular, 5-HT has been localized in many tunicate species but only a few studies have investigated its physiological functions. Tunicates, including ascidian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 90 publications
(142 reference statements)
1
9
0
Order By: Relevance
“…Kanamycin-resistant colonies were selected and cultured o/n purified with Plasmid Miniprep system (Promega) and verified by sequencing (Microsynth, Switzerland). PCR products with flanking T7 promoters were used as template for the synthesis of anti-sense riboprobes using a T7 RNA polymerase (Roche) (Mercurio et al 2023). Riboprobes were purified by precipitation with 0.1 M LiCl and 75% EtOH.…”
Section: Whole Mount Ishmentioning
confidence: 99%
“…Kanamycin-resistant colonies were selected and cultured o/n purified with Plasmid Miniprep system (Promega) and verified by sequencing (Microsynth, Switzerland). PCR products with flanking T7 promoters were used as template for the synthesis of anti-sense riboprobes using a T7 RNA polymerase (Roche) (Mercurio et al 2023). Riboprobes were purified by precipitation with 0.1 M LiCl and 75% EtOH.…”
Section: Whole Mount Ishmentioning
confidence: 99%
“…In the genome of Ciona, five genes corresponding to serotonin receptors have been identified (Mercurio et al, 2023). The phylogenetic analysis showed that two sequences, 5HT1.1 and 5HT1.2, are basal to all 5HT1 paralogs of vertebrates.…”
Section: The Serotonin Machinerymentioning
confidence: 99%
“…Next, to overcome 1D 1 H NMR overlapping signals, we performed a 2D 1 H- 13 C HSQC experiment, shown in Figure 3B. We highlighted three important regions in the spectrum.…”
Section: Microcosmus Exasperatus Viscera Presents a Dermatan Sulfate ...mentioning
confidence: 99%
“…Nuclear magnetic resonance (NMR, 1D, and 2D spectra) was performed for the SP1 fraction (2 mg) using a triple resonance probe (900 MHz Bruker, Karlsruhe, Germany). 1 H NMR 1D spectra were recorded using 32 scans with a 1.5-s inter-scan delay at 35 • C. 1 H/ 13 C HSQC (heteronuclear single quantum coherence) spectrum using time proportion phase incrementation (TPPI) for quadrature detection in the indirect dimension. A total of 64 scans and 1048 × 512 points were recorded.…”
Section: Nuclear Magnetic Resonance (Nmr) Analysesmentioning
confidence: 99%
See 1 more Smart Citation